Envisioning the Future of Literature in the Age of Globalisation: Bangladesh and Beyond - Quayum, Mohammad (SARE: Southeast Asian Review of English, 2023)
This article explores the present and future of literature in democratic societies and why literature and the humanities are indispensable for republics like Bangladesh. It investigates the silent crisis literature has been experiencing in the present age of globalisation with its increasing emphasis on STEM subjects in academia and concurrent dismissive attitude towards literature and the humanities as “feckless frills.” With the help of two South Asian short stories – Rabindranath Tagore’s “Kabuliwala” and R.K. Narayan’s “The House Opposite” – the article illustrates how the study of literature helps to create thoughtful, empathetic and imaginative citizens as well as vibrant and sturdy cultures, making it, therefore, imperative for building a healthy, harmonious and symmetrical civilisation. It concludes by advocating that the study of literature not only helps to create a moral centre in an otherwise material culture but can also provide the know-how to participate in and even advance the world of science, business and technology, thereby refuting the fallacy that it is impractical and therefore useless in the modern era.